Composing of Scenarios Development in Strategic Planning - MUKANOV, Aidar; SADUOV, Askar; AKBAYEV, Yerbolsyn; DULATBEKOVA, Zhanar; OSPANOVA, Anarkul; SELEZNEVA, Irina; MADIYAROVA, Elvira; JEMPEISSOVA, Gulnara (Journal of Environmental Management and Tourism, 2018)
Abstract : Today, there are different points of view on the strategic planning of the production activity at enterprises and approaches to its implementation. In conditions of high uncertainty and rapid changes in the surrounding environment developing a strategy, relying only on probabilistic forecast is too risky. In an unstable environment, there are many possible options of future, which raises the need to design scenarios for key areas of development. In addition, it should be noted that many Russian enterprises during strategic planning of production activities "thinking scenario" has not taken root. In part, it happened due to of complication of development process and identification of scenario’s reliability. Preparation of the scenarios required significant time, while in most cases the whole system of industrial relations in the domestic enterprises built with reliance on short-term goals. In the above scientific paper, the authors reveal some theoretical features of the strategic planning of production activities, the approaches formed in Russia according to strategic planning, as well as the importance of developing the scenarios in the planning of activities, which directed to achieve the strategic goals of the organization. The author notes that the main meaning of development scenarios for strategic planning of industrial activity is to construct different and equally plausible options for the production development in the future. It is emphasized that the development of scenarios should be one of basic conditions for the strategic planning of industrial activity, which is capable of quickly and effectively prepare the production process and the whole enterprise for the new economic conditions.